Narrativas en Responsabilidad Afectiva en 5 Parejas Swinger en la Ciudad de Bogotá. (2023)
The main objective of this research study is to characterize the narratives of emotional responsibility in swinger couples and their relationship with the couple's satisfaction and stability. For this purpose, a qualitative methodology was used, with a multiple case study design, based on a descriptive-exploratory scope and a phenomenological approach. Likewise, 5 swinger couples participated in the unstructured interviews, transcribing the interviews literally for their respective analysis.